2011
DOI: 10.1007/s10549-011-1599-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of unclassified variants in the BRCA1/2 genes with a putative effect on splicing

Abstract: A subset of the unclassified variants (UVs) identified during genetic screening of BRCA1/2 genes may affect splicing. We assessed at RNA level the effect of four BRCA1 and ten BRCA2 UVs with a putative splice effect, as predicted in silico. The variants selected for this study were beyond the positions -1, -2 or +1, +2 from the exon, and were not previously described (n = 8) or their effect on splicing was not assessed previously (n = 6). Lymphocytes from UV carriers and healthy controls were cultured and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 44 publications
6
34
0
1
Order By: Relevance
“…In addition, our analysis of BRCA2 c.8754?3G[C showed that this variant induced retention of 46 nucleotides in the transcript. This is in agreement with a very recent publication reporting splicing results for this variant [26] and is an effect similar to that previously reported for c.8754?1G[A [27]. Similarly, the detection of complete in-frame skipping of exon 3 from the mutant allele for BRCA2 c.316?5G[A is comparable to findings from Bonnet et al [16] for c.316?5G[C, and our study demonstrates the importance of quantifying the contribution of the variant allele to aberrant and variant transcripts when a variant is associated with upregulation of the naturally occurring delta exon 3 isoform identified in healthy controls.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, our analysis of BRCA2 c.8754?3G[C showed that this variant induced retention of 46 nucleotides in the transcript. This is in agreement with a very recent publication reporting splicing results for this variant [26] and is an effect similar to that previously reported for c.8754?1G[A [27]. Similarly, the detection of complete in-frame skipping of exon 3 from the mutant allele for BRCA2 c.316?5G[A is comparable to findings from Bonnet et al [16] for c.316?5G[C, and our study demonstrates the importance of quantifying the contribution of the variant allele to aberrant and variant transcripts when a variant is associated with upregulation of the naturally occurring delta exon 3 isoform identified in healthy controls.…”
Section: Discussionsupporting
confidence: 94%
“…For this purpose, we studied the variant using a previously described BRCA1 exon 11 minigene for the splicing assay [14]. Our results demonstrate an alteration of the process of splicing, similar to that observed previously by Dias Brandao et al [13]. Site-directed mutagenesis around position c.693 demonstrated a change in the splicing pattern and the presence of a composite regulatory element of splicing (CERES) [15,16] in BRCA1 exon 11.…”
Section: Introductionsupporting
confidence: 75%
“…We show that both when using RNA from a blood sample from a patient and in vitro (using a minigene for the splicing assay), the sequence variant increases Δ11 and decreases the Δ11q and full 11 isoforms of the BRCA1 gene, thus altering the balance of the BRCA1 isoforms (Figure 1 and Figure 2). Although this variant was not originally considered pathogenic [13], it is still possible that this variant leads to cancer predisposition. It is already known that BRCA1 exon 11 splicing isoforms are implicated in cancer [9,22,23], and maintaining the correct isoform proportions is important in preventing cell transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now evident that the unbalanced expression of splicing variants or the failure to properly express the correct isoforms is part of the biology of cancer cells (Pajares et al, 2007). For example, abnormal splicing profiles of the oncogenes BRCA1/2 and APC and tumor suppressive gene TP53 have been identified in breast, colorectal, and ovarian cancer cells (Brandão et al, 2011;Cheah et al, 2014;Marcel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%